The Effect of the Differentiated Learning Model on Pencak Silat Kicking Skills of Grade VIII Students at SMP Negeri 5 Karawang Barat. - Fatin Rizqi Utami; Dikdik Fauzi Dermawan; Rekha Ratri Julianti (Universitas Hamzanwadi, 2026)
The low pencak silat kicking skills of eighth-grade students at SMP Negeri 5 Karawang Barat became the main problem in this study. Learning was still dominated by demonstration and direct instruction methods, causing students to be passive and lack a comprehensive understanding of kicking techniques. This study aimed to determine the effect of differentiated learning on pencak silat kicking skills among eighth-grade students at SMP Negeri 5 Karawang Barat. The study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 42 students selected through purposive sampling. The research instrument was a pencak silat kicking skill test covering straight kicks, crescent kicks, and T-kicks, with validity r > 0.316 and reliability Cronbach's Alpha 0.826. Data were analyzed using descriptive statistics and Paired Sample t-Test. The results showed an increase in the average score from 50.31 in the pretest to 77.17 in the posttest. Hypothesis testing revealed a significance value of 0.000 (p < 0.05), indicating a significant effect of differentiated learning on students' pencak silat kicking skills. The study concludes that differentiated learning is effective in improving pencak silat kicking skills and can be used as an alternative instructional strategy in physical education to accommodate differences in students' abilities, interests, and learning styles.